PENDAMPINGAN BELAJAR MATEMATIKA DAN BAHASA INGGRIS GRATIS UNTUK ANAK ASUH YAYASAN AL-KAMILAH - Angga Hidayat; Anita Anggraini; Yuliana Friska; Ani Kusumaningsih; Moh. Thoyib Syafi’i (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
The part that needs to be improved from a student living in Al-Kamilah Foundation from an academic perspective is the ability to count and speak English. The service team teaches regularly at the Al-Kamilah Foundation once a week, to be precise on Wednesdays, to improve the numeracy skills and English of the foster children at the Foundation. Continuous training is needed to have a profound effect on increasing this ability. Teaching is carried out by lecturers from Pamulang University who have an educational background both from a scientific background in mathematics and English. The training has provided significant improvement results because this program has actually been going on for 3 semesters which are carried out continuously every week, unless it is closed during holidays and class holidays